2008
DOI: 10.1088/0953-2048/21/3/034010
|View full text |Cite
|
Sign up to set email alerts
|

Low-power superconducting motors

Abstract: Since the discovery and development of adequate superconducting materials, the development of motors has been a challenge for applications. The basis of design, however, has been the substitution of copper wires by superconducting tapes in coils in order to obtain a higher working field, thus improving power density and efficiency.In the case of high-power motors, the benefit is clear. The cost of the materials, cryogenics and building procedures could be assumed by the clear benefit in size, weight, efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…6. It is shown that the mitigation effect during the applied timevarying field stage (second stage) contributed by the ferromagnetic surface shield is relatively large when B ex = 0.1 T, compared with the case where B ex = 0.3 T. The mitigation performance of the ferromagnetic surface shield is a passive effect, which means if the magnitude of applied field is below the saturation field and the final trapped field near the ferromagnetic surface is relatively high, the enhancement performance will be also high as shown in equation (5):…”
Section: B Surface Shieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…6. It is shown that the mitigation effect during the applied timevarying field stage (second stage) contributed by the ferromagnetic surface shield is relatively large when B ex = 0.1 T, compared with the case where B ex = 0.3 T. The mitigation performance of the ferromagnetic surface shield is a passive effect, which means if the magnitude of applied field is below the saturation field and the final trapped field near the ferromagnetic surface is relatively high, the enhancement performance will be also high as shown in equation (5):…”
Section: B Surface Shieldingmentioning
confidence: 99%
“…arge, single-grain (RE)BCO high-temperature superconducting (HTS) bulk materials have great potential to trap high magnetic fields of over 17 T below 30 K [1], [2] and up to3 T at 77 K [3]. More compact and high-performance applications can be realized by using HTS bulks [4][5][6][7][8][9][10][11], but in practical applications these can be exposed to time-varying magnetic field perturbations. Since this phenomenon affects the magnetic field trapped in the bulks to a large extent, the overall efficiency and performance can be limited.…”
Section: Introductionmentioning
confidence: 99%
“…The common point of the investigations mentioned above is that they refer usually to a relatively "low" number of transverse ac cycles (typically up to 100-1000) with a "large" amplitude (typically from 0.1 Hp to several times Hp, where Hp denotes the full-penetration field). In applications such as magnetic bearings and brushless ac machines [46][47][48][49][50][51][52], however, the transverse fields of small amplitude are applied repeatedly for a long time. This is precisely the regime studied in the present work.…”
Section: Introductionmentioning
confidence: 99%
“…Highly sensitive magnetic measurement systems, such as in a biomagnetic imaging device, need efficient magnetic shields for reducing the effects of the external magnetic disturbances [4,5,6]. Powerful magnets are required in magnetic bearing systems, where they produce large levitation forces [7,8], or in rotating machines, where they produce a large torque on the shaft [9,10,11].…”
Section: Introductionmentioning
confidence: 99%